1997
DOI: 10.1590/s0103-84781997000300025
|View full text |Cite
|
Sign up to set email alerts
|

Implementação da seleção recorrente no melhoramento de plantas autógamas através da macho-esterilidade

Abstract: Os sistemas de melhoramento convencionais baseados no método genealógico, utilizados principalmente em cereais de estação fria, determinam a redução da variabilidade e da capacidade de recombinação, devido a utilização de um número de genitores limitado nos cruzamentos. O incremento da probabilidade de recombinação através da seleção recorrente pelo aumento do número de cruzamentos pode ser a saída para este problema. A utilização da macho-esterilidade representa uma alternativa viável para propiciar o cruzame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
2
0
3
Order By: Relevance
“…Another option would be the use of multiple crossings between accessions of exotic germplasm and non-kin elite genotypes, or genotypes with a small degree of kinship. A third strategy consists of using recurrent selection for composition of populations with a broad genetic base; nevertheless, the high cost of implementation of this method impedes its adoption in breeding programs (Canci et al 1997). …”
Section: Resultsmentioning
confidence: 99%
“…Another option would be the use of multiple crossings between accessions of exotic germplasm and non-kin elite genotypes, or genotypes with a small degree of kinship. A third strategy consists of using recurrent selection for composition of populations with a broad genetic base; nevertheless, the high cost of implementation of this method impedes its adoption in breeding programs (Canci et al 1997). …”
Section: Resultsmentioning
confidence: 99%
“…Inbreeding, or the likelihood of two randomly taken alleles, in a single locus, to be identical by descent, limits the possibility of new gene combinations in their offspring. The narrow genetic base and self-fertilization processes produce gene blocks that reduce the potential for recombination in offspring (Canci et al 1997). Studies estimating recombination rates in Arabidopsis reported that the absence of differences between homologous chromosomes reduced the recombination rate potential (Salomé et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Portanto, foram nomeadas a população AR, proveniente dos campos de produção de sementes de São Borja, RS, Brasil e a população UR, coletada nos campos de produção de sementes na cidade de Melo/Cerro Largo, Uruguai. Ressalta-se a elevada variabilidade intrapopulacional observada, possivelmente favorecida pela taxa de fecundação cruzada que, nesta espécie e em condições mais favoráveis, pode chegar a até 30% com o auxílio de polinizadores (Canci et al, 1997).…”
Section: Methodsunclassified